(untitled) (Research, Society and Development, 2020)
In order to evaluate and characterize urban drainage systems, several studies and methodologies have been developing to find a better way to make efficient and solve the problems generated, whether environmental, legal or economic, in urban drainage systems. The objective of this work was to review the evaluation and characterization or diagnosis methodologies applied to urban drainage systems. The bibliographic research was used as a methodological basis on the subject for the development of its work. As a result, it was possible to verify that there are still issues in methods of characterization of drainage systems. The most usual ones are being used, however, regarding the evaluation of drainage systems, one can find several methods that allow the best performance of these systems. In conclusion, there is no specific method for both evaluation and characterization of the drainage system since it depends on the proposed objectives in each methodology and it is also possible to use more than one methodology within the same objective.